Macrophage Migration Inhibitory Factor in Fetoplacental Tissues from Preeclamptic Pregnancies with or without Fetal Growth Restriction - Simona Cardaropoli; Luana Paulesu; Roberta Romagnoli; Francesca Ietta; Daniela Marzioni; Mario Castellucci; Alessandro Rolfo; Elena Vasario; Ettore Piccoli; Tullia Todros (Clinical and Developmental Immunology)
The proinflammatory cytokine MIF (macrophage migration inhibitory factor) is involved in physiological and pathological processes in pregnancy. MIF maternal serum levels are increased in preeclampsia (PE). We hypothesize that pregnancy tissues are the source of MIF overexpression in PE. MIF protein was studied in maternal sera, placental tissues, fetal membranes, and umbilical cord of 8 control and 20 PE pregnancies: 10 with normal fetal growth (PE-AGA) and 10 with fetal growth restriction (PE-FGR). MIF levels were significantly higher in PE-AGA membranes than in controls and PE-FGR. In PE-FGR, MIF cord concentrations were higher than in PE-AGA while MIF placental levels were lower than in controls. MIF maternal serum levels were higher in PE, compared to controls, and the difference was mainly due to PE-FGR samples. These data support MIF involvement in PE pathogenesis and suggest that different pregnancy tissues contribute to MIF production in PE with and without fetoplacental compromise.